2011
DOI: 10.1177/0020872811418993
|View full text |Cite
|
Sign up to set email alerts
|

The nature of employer’s involvement in social work education: An international exploration

Abstract: Email interviews and internet inquiries were used to explore the nature and extent of employer engagement in qualifying social work education programmes across 10 countries: and USA. Findings indicate considerable variations in the nature and extent of engagement in admissions processes, programme management and assessment of student competence. Practice learning/field education was the main area for employer engagement. The desirability of employer engagement is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Participants offered numerous examples of the ways that programs were creatively supporting students to experience developmental social work, through enhancing their practice curriculum, orchestrating practice opportunities, and creating new placements. The good news from this research is that the pedagogical commitment of social work programs in Southern and East Africa appears to have resulted in a continuation − and perhaps an enhancement − of the creativity and ingenuity identified in earlier studies (Ferguson & Smith, 2012;Lombard, 1997Shardlow et al, 2011Simpson & Sathiparsad, 2011).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Participants offered numerous examples of the ways that programs were creatively supporting students to experience developmental social work, through enhancing their practice curriculum, orchestrating practice opportunities, and creating new placements. The good news from this research is that the pedagogical commitment of social work programs in Southern and East Africa appears to have resulted in a continuation − and perhaps an enhancement − of the creativity and ingenuity identified in earlier studies (Ferguson & Smith, 2012;Lombard, 1997Shardlow et al, 2011Simpson & Sathiparsad, 2011).…”
Section: Resultsmentioning
confidence: 69%
“…There were also claims that the practice of fieldwork in Africa was often constrained by external factors leaving it subordinate in status to, and less rigorous than, on-campus academic activity (Dhemba, 2012;Kaseke, in Bar-On, 2001). For example, studies consistently found increased competition between academic institutions for, and an acute shortage of, relevant placements (Chitereka, 2009;Dhemba, 2012;Dziro, 2013;Hochfeld et al, 2009;Hoffman, 1993;Shardlow, Scholar, Munro, & McLaughlin, 2011). With only limited placements available -as well as financial constraints for students and social work programs -fieldwork opportunities were often geographically limited, possibly resulting in compromised learning (Chogugudza, 2009;Dhemba, 2012;Dziro, 2013).…”
Section: Knowledge About Fieldwork In Southern and East Africamentioning
confidence: 99%
See 1 more Smart Citation
“…In turning to the literature to find answers to the questions posed, the study by Shardlow et al (2011) of the nature and extent of employer engagement in qualifying social work education programmes across 10 countries (including South Africa) found the following:…”
Section: Promoting Social Work Graduates' Employment Through the Socimentioning
confidence: 99%
“…Apart from the abovementioned summary of the findings from the study by Shardlow et al (2011) This lacuna in the body of knowledge on employers' perspectives on the employability of NQSWs, in view of promoting graduates' employment by informing the Social Work curriculum, is regarded as the research problem for the proposed study. Creswell (2016:88) classifies this as a "literature-related" problem, because "the topic has been understudied", and "there is little research on the topic."…”
Section: Promoting Social Work Graduates' Employment Through the Socimentioning
confidence: 99%